Nonlinear Local Deformations of Red Blood Cell Membranes: Effects of Toxins and Pharmaceuticals (Part 2) - Alexander M. Chernysh; Elena K. Kozlova; Viktor V. Moroz; Viktoria A. Sergunova; Olga E. Gudkova; Alexander P. Kozlov; Ekaterina A. Manchenko (Общая реаниматология, 2018)
Modifiers of membranes cause local defects on the cell surface. Measurement of the rigidity at the sites of local defects can provide further information about the structure of defects and mechanical properties of altered membranes.The purpose of the study: a step-by-step study of the process of a nonlinear deformation of red blood cells membranes under the effect of modifiers of different physico-chemical nature.Materials and methods. The membrane deformation of a viscoelastic composite erythrocyte construction inside a cell was studied by the atomic force spectroscopy. Nonlinear deformations formed under the effect of hemin, Zn2+ ions, and verapamil were studied.Results. The process of elastic deformation of the membrane with the indentation of a probe at the sites of local defects caused by modifiers was demonstrated. The probe was inserted during the same step of the piezo scanner z displacement; the probe indentation occured at the different discrete values of h, which are the functions of the membrane structure. At the sites of domains, under the effect of the hemin, tension areas and plasticity areas appeared. A mathematical model of probe indentation at the site of membrane defects is presented.Conclusion. The molecular mechanisms of various types of nonlinear deformations occurring under the effect of toxins are discussed. The results of the study may be of interest both for fundamental researchers of the blood cell properties and for practical reanimatology and rehabilitology.